Morphometric analysis of the acromion process of the scapula - Ananya Priya; Anjali Jain (Wolters Kluwer Medknow Publications, 2020)
Context: This study was done to analyze the morphometric parameters of the acromion process of human scapulae. The knowledge of morphometry of acromion process is vital for orthopedic surgeons while performing surgeries like acromioplasty for the treatment of subacromial impingement syndrome and repair of rotator cuff tears. Aims: The aim was to study the morphometry of the acromion process of the scapula. Settings and Design: The study was conducted on 105 adult dry human scapulae of unknown age and sex. All damaged human scapulae were excluded from the present study. Subjects and Methods: Length, breadth, thickness of acromion process, coraco-acromial distance, and acromioglenoid distance were measured in millimeter using digital Vernier caliper. Statistical Analysis Used: Data were tabulated. Mean and standard deviation for each parameter were calculated using SPSS version 16.0. Results: The mean acromial length was 41.65 ± 7.57 mm, acromial width was 24.50 ± 2.91 mm, acromial thickness was 7.62 ± 1.34 mm, coracoacromial distance was 33.35 ± 6.12 mm, and acromioglenoid distance was 29.41 ± 4.65 mm. Conclusions: The data obtained in the current study can add to the knowledge that can aid in surgical procedures around the shoulder joint.